{Nano-gold, iron(III)-1,3,5-benzene tricarboxylate metal organic framework (MOF)} nano-composite as precursor for laser ablation generation of gold-iron Aum Fen +/- (m = 1-35, n = 1-5) clusters. Mass spectrometric study - Pečinka, Lukáš; Havel, Josef (Rapid communications in mass spectrometry, 2020)
RATIONALE: Gold-iron bimetallic materials have applications in many fields, especially in nanotechnology and biomedicine. The chemistry of iron-doped gold clusters is still not fully understood but opens up the possibility of developing new materials, e.g. of gold cages doped with iron atoms. There have been several theoretical studies on these clusters but only a few experimental studies. METHODS: Laser desorption ionisation (LDI) was used for the generation of Au-Fe bimetallic clusters via laser ablation (337 nm nitrogen laser) of the synthesised nano-composite {nano-gold; Fe(III) 1,3,5-benzene tricarboxylate}, i.e. {AuNPs, Fe-MOF}, while a quadrupole ion trap time-of-flight mass spectrometer, equipped with a reflectron, was used to acquire mass spectra. RESULTS: A {AuNPs, Fe-MOF} nano-composite was prepared and found suitable for the LDI generation of Aum Fen clusters. In addition to Aum +/- (m = 1-35) clusters, a series of positively and negatively charged gold-iron Aum Fen +/- clusters were generated. The mass spectra exhibited evidence for the clusters containing up to five iron atoms. In total, 113 binary Aum Fen +/- clusters (m = 1-35, n = 1-5) were identified in the gas phase. CONCLUSIONS: A synthesised {AuNPs, iron(III)-1,3,5-benzene tricarboxylate MOF} nano-composite was found suitable for the generation of many new gold-iron clusters and mass spectrometry was shown to be an efficient technique for the determination of the cluster stoichiometry. A broad series of over 100 bimetallic Aum Fen clusters, some of them suggested to be gold cages doped with iron atoms (for m = 12 and higher), not only demonstrate a rich and complex chemistry, but also open wide possibilities of biomedical applications.